A brief review on the recent evolution in piezoelectric linear ultrasonic motors. (2nd December 2021) - Mukhopadhyay, Shalini; Behera, Basudeba; Kumar, Jayendra
Abstract: This article represents the various recent advancements in the field of Piezoelectric Ultrasonic Motors, especially in linear type. The construction and operation principles evolving time to time. We have accumulated and presented a brief discussion on the linear ultrasonic motor including its working principles, initial designs, and recent advancements in this article. These motors have had increasing applications in recent years and have been developing rapidly due to their simplicity of construction and good performance. The potential applications are expanding lately to various areas such as medical devices, precise positioning systems, astronautical devices, tactile feedback systems, and many more. Owing to the wide range of applications, simple and compact design, rapidly increasing miniaturization, and the several advantages of the linear ultrasonic motor, it has been a vastly researched area in the last few decades. Continuous effort is being put into creating smaller and efficient designs, structures, and materials of the device, with stable and upgraded output performance, an acceptable range of frictional wear enabling prolonged usage.